Method for improving performance of zirconium alloy Cr coating and method for detecting performance of Cr coating

By grinding, ion cleaning and deposition of the base layer of the zirconium alloy matrix, and depositing the Cr coating with multi-arc ion plating technology and high-temperature annealing heat treatment, the dispersion problems of the existing Cr coating in terms of oxidation corrosion resistance, wear resistance and mechanical properties are solved, and the crack resistance and interface binding properties of the Cr coating are significantly improved.

CN119685761AInactive Publication Date: 2025-03-25SUN YAT SEN UNIV

Patent Information

Application Number
CN202411838495.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing Cr coatings have great dispersion in terms of oxidation corrosion resistance, wear resistance, mechanical properties, etc., and are prone to surface microcracks, interface cracks and even peeling under external loading, which cannot meet the 1% circumferential strain requirement of fuel cladding.

Method used

By grinding and ultrasonic cleaning of the zirconium alloy matrix, high-energy ions formed by evaporation and ionization of arc discharge targets are used to ion cleaning and deposit the base layer. Then, the Cr coating is deposited using multi-arc ion plating technology and high-temperature annealing heat treatment from 650°C to 700°C.

Benefits of technology

It significantly improves the crack resistance and interface bonding properties of the Cr coating, enhances the binding force between the Cr coating and the substrate, reduces interface cracks and peeling, and meets the structural integrity requirements of the fuel cladding under high strain.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119685761A_ABST
    Figure CN119685761A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of metal material surface treatment, in particular to a method for improving the performance of a zirconium alloy Cr coating and a method for detecting the performance of the Cr coating, and the method for improving the performance of the zirconium alloy Cr coating comprises the steps that the surface of a zirconium alloy matrix is polished; the method comprises the following steps: cleaning a zirconium alloy matrix by using high-energy ions formed by evaporation and ionization of an arc discharge target material, depositing a base coat, and depositing a Cr coating on the zirconium alloy matrix by using a multi-arc ion plating technology; and carrying out high-temperature annealing heat treatment on the Cr coating. According to the method, the cracking resistance and the interface bonding performance of the Cr coating can be effectively improved. The method for detecting the performance of the Cr coating comprises the following steps: preparing a zirconium alloy matrix sample of the Cr coating which contains a base coat and is subjected to heat treatment; preparing a zirconium alloy matrix sample which does not contain a base coat and is not subjected to heat treatment of a Cr coating; preparing a zirconium alloy matrix sample containing a base coat and a Cr coating which is not subjected to heat treatment; and evaluating the toughness and cracking resistance of the Cr coating by comparing the initial strain of the first crack and the saturated crack density of each Cr coating sample.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of metal material surface treatment, and in particular to a method for improving the performance of a zirconium alloy Cr coating and a method for detecting the performance of the Cr coating. Background Art

[0002] Accident-resistant fuel Cr coating cladding is the mainstream solution for the new generation of nuclear fuel systems to enhance their ability to resist accidents. The accident-resistant Cr coating solution can not only significantly improve the oxidation corrosion resistance of the fuel cladding under severe accident conditions, but also maintain the existing technical process of the fuel elements, inherit the excellent performance and database of the existing fuel, and become the technical solution with the most application potential in recent years. The accident-resistant Cr coatings developed in recent years include MAX phase, carbide, nitride, metal Cr coating and composite Cr coating. Among the many accident-resistant Cr coating solutions, Cr coating has better and more balanced comprehensive performance in terms of oxidation corrosion resistance, wear resistance, mechanical properties similar to the substrate and thermal expansion coefficient, and is considered to be the most promising candidate material for accident-resistant Cr coating.

[0003] The mainstream Cr coating preparation processes include physical vapor deposition (such as arc ion plating and magnetron sputtering), chemical vapor deposition, cold spraying, etc. A large number of previous studies have shown that the preparation process and parameters of Cr coatings significantly affect the microstructure, texture, defects, interface bonding performance, etc. of Cr coatings, which in turn affect the oxidation resistance and mechanical properties of Cr coatings. However, various types of Cr coatings prepared internationally and domestically have large dispersion in terms of oxidation resistance, wear resistance, and mechanical properties. Structural integrity is the basic condition to ensure the good performance of Cr coatings. Under the action of external loads, surface microcracks, interface cracks, and even peeling will occur inside the Cr coating, and the zirconium cladding will lose its protective effect and cause potential hydrogen explosion risks. Because the Cr coating has a high ductile-brittle transition temperature, under the action of external loads, the Cr coating exhibits typical brittle cracking characteristics, and the cracking strain is less than 0.5%, which cannot meet the industry requirements of the fuel cladding to resist 1% hoop strain. In addition, the interface bonding performance of the Cr coatings currently prepared is generally poor, and interface cracks and even peeling are prone to occur under external loads. The anti-cracking performance and interface bonding performance of the Cr coating directly affect the structural integrity of the Cr coating cladding under service conditions and severe accident conditions. Summary of the invention

[0004] The present application aims to solve at least one of the above-mentioned technical problems in the prior art to a certain extent. To this end, the present application embodiment provides a method for improving the performance of zirconium alloy Cr coating and a method for detecting the performance of Cr coating. The method of the present application can effectively improve the anti-cracking performance and interface bonding performance of Cr coating.

[0005] A method for improving the performance of a zirconium alloy Cr coating comprises the following steps: Zirconium alloy matrix pretreatment: polish the upper and lower surfaces and sides of the zirconium alloy matrix, and remove surface stains by ultrasonic cleaning; Deposition of Cr coating on zirconium alloy substrate: The zirconium alloy substrate is cleaned by high-energy ions formed by arc discharge target evaporation and ionization, and a high bias voltage and low gas pressure are used for a long time to deposit the base layer, so that the high-energy incident ions are pinned to the surface of the zirconium alloy substrate. The bias voltage of the arc discharge is -500V, the arc target current is 100A, the coil current is 1A, the gas pressure is 0.6Pa, and the base layer deposition time is 30min. Then, the Cr coating is deposited on the zirconium alloy substrate by multi-arc ion plating technology. When depositing the Cr coating, the bias voltage of the arc discharge is -75V, the arc target current is 100A, the coil current is 1A, the gas pressure is 2.7Pa, the zirconium alloy substrate temperature is 340℃, and the deposition time is 6h. Heat treatment of zirconium alloy substrate: The zirconium alloy substrate on which the Cr coating is deposited is subjected to high-temperature annealing heat treatment, wherein the heat treatment temperature is greater than the ductile-brittle transition temperature of the Cr coating and less than the recrystallization temperature of the zirconium alloy substrate.

[0006] In an optional or preferred embodiment, before the high-temperature annealing heat treatment, the zirconium alloy substrate after the Cr coating is deposited is placed in a quartz tube for vacuum packaging. After the high-temperature annealing heat treatment is completed, it is naturally cooled to room temperature in an air environment, and then the quartz tube is broken to take out the heat-treated Cr-coated zirconium alloy substrate.

[0007] In an optional or preferred embodiment, the steps of placing the zirconium alloy substrate into a quartz tube for vacuum packaging are: placing the zirconium alloy substrate in a quartz tube, passing argon gas into the tube for 10 minutes, and then using a vacuum pump to pump the gas in the tube into a vacuum state, and then using a tungsten wire to heat the other end of the quartz tube to a high-temperature molten state and achieve packaging to ensure that there is no oxygen in the tube.

[0008] In an optional or preferred embodiment, the steps of high temperature annealing heat treatment are: the muffle furnace is heated to a target temperature at a rate of 10°C / min, the target temperature is 650°C~700°C, then kept warm for 30 minutes, and then the furnace door is opened, and the packaged Cr-coated zirconium alloy substrate is quickly placed in a crucible boat in the muffle furnace for high temperature annealing heat treatment. After the temperature stabilizes to the target temperature, it is kept warm for 1 hour.

[0009] In an optional or preferred embodiment, the Cr-coated zirconium alloy substrate taken out from the quartz tube after cooling after heat treatment is placed in an anhydrous ethanol solution for ultrasonic cleaning.

[0010] A method for detecting the performance of a Cr coating, characterized in that it comprises the following steps: According to the method described above, a zirconium alloy substrate sample containing a primer layer and a heat-treated Cr coating was prepared; A zirconium alloy substrate sample without a primer layer and without a heat-treated Cr coating is prepared; A zirconium alloy substrate sample containing a primer layer and a Cr coating without heat treatment is prepared; The observation surfaces of the above three samples were ground and polished until the Cr coating and the substrate cross section were exposed for in-situ observation of the crack evolution information of the sample cross section. The samples were placed on the testing machine, the upper and lower pressure heads were pressed tightly, and a preload of 20N was applied to fix them. Then the three-point bending test was started. The speed of the pressure head moving downward was 0.005 mm / s. At the same time, a high-power optical microscope was used to take real-time photos of the cross-sectional morphology of the Cr coating samples to obtain the evolution data of the Cr coating crack density at different deflections. The Cr coating crack density is defined as the number of Cr coating cracks per unit area. When the deflection reaches a specific value, the test is stopped, the sample is taken out after unloading, and the test is ended. The crack density data of the sample is counted, and the toughness and crack resistance of the Cr coating are evaluated by comparing the first crack initiation strain and saturated crack density of each Cr coating sample.

[0011] In an optional or preferred embodiment, the steps of preparing a zirconium alloy substrate sample without a primer layer and without a heat-treated Cr coating are as follows: Step 1: Cut the zirconium alloy plate into a number of three-point bending test samples, grind the upper and lower surfaces and sides of the samples with sandpaper, and then perform ultrasonic cleaning on the samples; Step 2: Place the Cr target with a purity of 99.99% in the multi-arc ion plating furnace, adjust the distance between the target and the sample to 20 cm, and perform ion cleaning on the sample surface before Cr coating. The ion cleaning is mainly divided into two steps: first, evacuate the furnace chamber to a vacuum of 1.0×10 -4 Pa, set the workpiece holder to a high bias and introduce argon gas, set a high bias of -600V to ionize the argon gas into Ar+ ions and bombard the sample surface at high speed, then turn on the arc source, and use the high-energy ions formed by the evaporation and ionization of the arc discharge target to clean the sample, then enter the Cr coating deposition stage, and deposit the Cr coating on the sample by multi-arc ion plating technology. The selected bias voltage is -75V, the arc target current is 100A, the coil current is 1A, the gas pressure is 2.7Pa, the zirconium alloy substrate temperature is 340℃, and the deposition time is 6h.

[0012] In an optional or preferred embodiment, the steps of preparing a zirconium alloy substrate sample containing a primer layer and a Cr coating layer that has not been heat-treated are as follows: Step 1: Cut the zirconium alloy plate into a number of three-point bending test samples, grind the upper and lower surfaces and sides of the samples with sandpaper, and then perform ultrasonic cleaning on the samples; Step 2: Place the Cr target with a purity of 99.99% in the multi-arc ion plating furnace, adjust the distance between the target and the sample to 20 cm, and perform ion cleaning on the sample surface before Cr coating. The ion cleaning is mainly divided into two steps: first, evacuate the furnace chamber to a vacuum of 1.0×10 -4 Pa, set the workpiece support high bias and pass argon gas, set -600V high bias to ionize argon into Ar+ ions and bombard the sample surface at high speed, then turn on the arc source, use the high-energy ions formed by the evaporation and ionization of the arc discharge target to clean the sample, then enter the deposition base layer stage, use the high-energy ions formed by the evaporation and ionization of the arc discharge target to clean the zirconium alloy substrate, use high bias and low gas pressure for a long time to deposit the base layer, so that the high-energy incident ions are pinned to the surface of the zirconium alloy substrate sample, the selected bias is -500V, the arc target current is 100A, the coil current is 1A, the gas pressure is 0.6 Pa, and the base layer deposition time is 30min, then enter the Cr coating deposition stage, and deposit the Cr coating on the sample by multi-arc ion plating technology, the selected bias is -75V, the arc target current is 100A, the coil current is 1A, the gas pressure is 2.7Pa, the zirconium alloy substrate temperature is 340℃, and the deposition time is 6h.

[0013] In an alternative or preferred embodiment, the deflection is the downward displacement of the indenter.

[0014] In an alternative or preferred embodiment, the test is stopped when the deflection reaches 1.7 mm.

[0015] Based on the above technical scheme, the embodiments of the present application have at least the following beneficial effects: in the method of the present application, the reverse sputtering effect generated by ion cleaning is beneficial to increase the roughness of the substrate surface and improve the bonding force between the Cr coating and the substrate. The base layer near the interface is a nano-fine crystal region and is pinned to the substrate surface. Due to the fine crystal strengthening effect of the base layer, cracks are hindered from initiating and expanding from the interface, thereby improving the crack resistance and interface bonding performance of the Cr coating. After heat treatment, the Cr coating undergoes recrystallization and grain growth, and the residual stress and initial dislocation density of the Cr coating are greatly reduced, while the plasticity and toughness are significantly improved. In addition, the heat treatment also greatly restores the interface grain boundary damage caused by the pinning effect of high-energy ions at the interface, further improving the crack resistance and interface bonding performance of the Cr coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] The present application is further described below with reference to the accompanying drawings and embodiments; Figure 1 The surface morphology and cross-sectional morphology of the Cr coating containing a primer layer and heat-treated at 700°C in the present application; Figure 2 is the crack density evolution curve of different Cr coating samples in this application; Figure 3 is the saturated crack density and the first crack initiation strain of different Cr coating samples in this application; Figure 4 The cross-sectional morphologies of different Cr coating samples after the three-point bending test in this application. DETAILED DESCRIPTION

[0017] In order to enable those skilled in the art to better understand the technical solutions in the present application, the technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work should fall within the scope of protection of the present application.

[0018] The following is a further detailed description of the implementation of the present application in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present application but cannot be used to limit the scope of the present application.

[0019] In the description of the embodiments of the present application, it should be noted that the terms "center", "longitudinal", "lateral", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the accompanying drawings, which are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the embodiments of the present application. In addition, the terms "first", "second", and "third" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance.

[0020] In the description of the embodiments of the present application, it should be noted that, unless otherwise clearly specified and limited, the terms "connected" and "connection" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be directly connected or indirectly connected through an intermediate medium. For ordinary technicians in this field, the specific meanings of the above terms in the embodiments of the present application can be understood according to specific circumstances.

[0021] In the embodiments of the present application, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may mean that the first and second features are in direct contact, or that the first and second features are in indirect contact through an intermediate medium. Moreover, a first feature being "above", "above" and "above" a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being "below", "below" and "below" a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.

[0022] Accident-resistant fuel Cr coating cladding is the mainstream solution for the new generation of nuclear fuel systems to enhance their ability to resist accidents. The accident-resistant Cr coating solution can not only significantly improve the oxidation corrosion resistance of the fuel cladding under severe accident conditions, but also maintain the existing technical process of the fuel elements, inherit the excellent performance and database of the existing fuel, and become the technical solution with the most application potential in recent years. The accident-resistant Cr coatings developed in recent years include MAX phase, carbide, nitride, metal Cr coating and composite Cr coating. Among the many accident-resistant Cr coating solutions, Cr coating has better and more balanced comprehensive performance in terms of oxidation corrosion resistance, wear resistance, mechanical properties similar to the substrate and thermal expansion coefficient, and is considered to be the most promising candidate material for accident-resistant Cr coating.

[0023] The mainstream Cr coating preparation processes include physical vapor deposition (such as arc ion plating and magnetron sputtering), chemical vapor deposition, cold spraying, etc. A large number of previous studies have shown that the preparation process and parameters of Cr coatings significantly affect the microstructure, texture, defects, interface bonding performance, etc. of Cr coatings, which in turn affect the oxidation resistance and mechanical properties of Cr coatings. However, various types of Cr coatings prepared internationally and domestically have large dispersion in terms of oxidation resistance, wear resistance, and mechanical properties. Structural integrity is the basic condition to ensure the good performance of Cr coatings. Under the action of external loads, surface microcracks, interface cracks, and even peeling will occur inside the Cr coating, and the zirconium cladding will lose its protective effect and cause potential hydrogen explosion risks. Because the Cr coating has a high ductile-brittle transition temperature, under the action of external loads, the Cr coating exhibits typical brittle cracking characteristics, and the cracking strain is less than 0.5%, which cannot meet the industry requirements of the fuel cladding to resist 1% hoop strain. In addition, the interface bonding performance of the Cr coatings currently prepared is generally poor, and interface cracks and even peeling are prone to occur under external loads. The anti-cracking performance and interface bonding performance of the Cr coating directly affect the structural integrity of the Cr coating cladding under service conditions and severe accident conditions.

[0024] Reference Figures 1 to 4 The present application provides a method for improving the performance of a zirconium alloy Cr coating, comprising the following steps: Zirconium alloy matrix pretreatment: polish the upper and lower surfaces and sides of the zirconium alloy matrix, and remove surface stains by ultrasonic cleaning; Deposition of Cr coating on zirconium alloy substrate: The zirconium alloy substrate is cleaned by high-energy ions formed by arc discharge target evaporation and ionization, and then a high bias voltage and low gas pressure are used to deposit the base layer for a long time, so that the high-energy incident ions are pinned to the surface of the zirconium alloy substrate. The bias voltage of the arc discharge is -500V, the arc target current is 100A, the coil current is 1A, the gas pressure is 0.6Pa, and the base layer deposition time is 30min. Then, the Cr coating is deposited on the zirconium alloy substrate by multi-arc ion plating technology. When depositing the Cr coating, the bias voltage of the arc discharge is -75V, the arc target current is 100A, the coil current is 1A, the gas pressure is 2.7Pa, the zirconium alloy substrate temperature is 340℃, and the deposition time is 6h. Heat treatment of zirconium alloy substrate: The zirconium alloy substrate on which the Cr coating is deposited is subjected to high-temperature annealing heat treatment, wherein the heat treatment temperature is greater than the ductile-brittle transition temperature of the Cr coating and less than the recrystallization temperature of the zirconium alloy substrate.

[0025] In the method of the present application, the reverse sputtering effect produced by ion cleaning is beneficial to increase the roughness of the substrate surface and improve the bonding force between the Cr coating and the substrate. The base layer near the interface is a nano-fine crystal region and is pinned to the substrate surface. Due to the fine crystal strengthening effect of the base layer, cracks are hindered from initiating and expanding from the interface, thereby improving the crack resistance and interface bonding performance of the Cr coating. After heat treatment, the Cr coating undergoes recrystallization and grain growth, and the residual stress and initial dislocation density of the Cr coating are greatly reduced, while the plasticity and toughness are significantly improved. In addition, the heat treatment also greatly restores the interface grain boundary damage caused by the pinning effect of high-energy ions at the interface, further improving the crack resistance and interface bonding performance of the Cr coating.

[0026] Under external load at room temperature, compared with the Cr coating without deposition base layer and without heat treatment, the surface crack density of the Cr coating with deposition base layer and heat treatment is greatly reduced, the crack resistance of the Cr coating is improved, and the interface cracks are significantly reduced or no interface cracks are observed. Even in the large plastic deformation area near the fracture, there are still no obvious interface cracks and interface peeling, indicating the excellent crack resistance and interface bonding performance of the Cr coating.

[0027] In order to avoid oxidation of the zirconium alloy substrate surface, in some embodiments, before the high-temperature annealing heat treatment, the zirconium alloy substrate after the Cr coating is deposited is placed in a quartz tube for vacuum packaging. After the high-temperature annealing heat treatment is completed, it is naturally cooled to room temperature in an air environment, and then the quartz tube is broken to take out the heat-treated Cr-coated zirconium alloy substrate.

[0028] In some embodiments, the steps of placing the zirconium alloy substrate into a quartz tube for vacuum packaging are as follows: placing the zirconium alloy substrate in a quartz tube, passing argon gas into the tube for 10 minutes, and then using a vacuum pump to pump the gas in the tube into a vacuum state, and then using a tungsten wire to heat the other end of the quartz tube to a high-temperature molten state and achieve packaging to ensure that there is no oxygen in the tube.

[0029] In some embodiments, the Cr-coated zirconium alloy substrate taken out from the quartz tube after cooling after heat treatment is placed in an anhydrous ethanol solution for ultrasonic cleaning.

[0030] In some embodiments, the muffle furnace is heated to a target temperature of 650°C to 700°C at a rate of 10°C / min, and then kept warm for 30 min. After that, the furnace door is opened, and the packaged Cr-coated zirconium alloy substrate is quickly placed in a crucible boat in the muffle furnace for high-temperature annealing heat treatment. After the temperature stabilizes to the target temperature, it is kept warm for 1 hour.

[0031] The Cr coating samples containing the base layer heat treated at 650℃~700℃ have more excellent and balanced properties.

[0032] The present application also provides a method for detecting the performance of a Cr coating, comprising the following steps: According to the method described above, a zirconium alloy substrate sample containing a primer layer and a heat-treated Cr coating was prepared; A zirconium alloy substrate sample without a primer layer and without a heat-treated Cr coating is prepared; A zirconium alloy substrate sample containing a primer layer and a Cr coating without heat treatment is prepared; The observation surfaces of the above three samples were ground and polished until the Cr coating and the substrate cross section were exposed for in-situ observation of the crack evolution information of the sample cross section. The samples were placed on the testing machine, the upper and lower pressure heads were pressed tightly, and a preload of 20 N was applied to fix them. Then the three-point bending test was started. The speed of the pressure head moving downward was 0.005 mm / s. At the same time, a high-power optical microscope was used to take real-time photos of the cross-sectional morphology of the Cr coating sample to obtain the evolution data of the Cr coating crack density at different deflections. The Cr coating crack density is defined as the number of Cr coating cracks per unit area. When the deflection reaches a specific value, the test is stopped, the sample is taken out after unloading, and the test is ended. The crack density data of the sample is counted, and the toughness and crack resistance of the Cr coating are evaluated by comparing the first crack initiation strain and saturated crack density of each Cr coating sample.

[0033] This method can effectively compare the performance of Cr coatings after deposition priming and heat treatment, Cr coatings without a primer layer and without heat treatment, and Cr coatings with a primer layer and without heat treatment.

[0034] In some embodiments, the steps for preparing a zirconium alloy substrate sample without a primer layer and without a heat-treated Cr coating are as follows: Step 1: Cut the zirconium alloy plate into a number of three-point bending test samples, grind the upper and lower surfaces and sides of the samples with sandpaper, and then perform ultrasonic cleaning on the samples; Step 2: Place the Cr target with a purity of 99.99% in the multi-arc ion plating furnace, adjust the distance between the target and the sample to 20 cm, and perform ion cleaning on the sample surface before Cr coating. The ion cleaning is mainly divided into two steps: first, evacuate the furnace chamber to a vacuum of 1.0×10 -4 Pa, set the workpiece holder to a high bias and introduce argon gas, set a high bias of -600V to ionize the argon gas into Ar+ ions and bombard the sample surface at high speed, then turn on the arc source, and use the high-energy ions formed by the evaporation and ionization of the arc discharge target to clean the sample, then enter the Cr coating deposition stage, and deposit the Cr coating on the sample by multi-arc ion plating technology. The selected bias voltage is -75V, the arc target current is 100A, the coil current is 1A, the gas pressure is 2.7Pa, the zirconium alloy substrate temperature is 340℃, and the deposition time is 6h.

[0035] In some embodiments, the steps for preparing a zirconium alloy substrate sample containing a primer layer and a Cr coating layer without heat treatment are as follows: Step 1: Cut the zirconium alloy plate into a number of three-point bending test samples, grind the upper and lower surfaces and sides of the samples with sandpaper, and then perform ultrasonic cleaning on the samples; Step 2: Place the Cr target with a purity of 99.99% in the multi-arc ion plating furnace, adjust the distance between the target and the sample to 20 cm, and perform ion cleaning on the sample surface before Cr coating. The ion cleaning is mainly divided into two steps: first, evacuate the furnace chamber to a vacuum of 1.0×10 -4 Pa, set the workpiece support high bias and introduce argon gas, set -600V high bias to ionize argon into Ar+ ions and bombard the sample surface at high speed, then turn on the arc source, use the high-energy ions formed by arc discharge target evaporation and ionization to clean the sample, and deposit the base layer. The selected bias is -500 V, the arc target current is 100A, the coil current is 1A, the gas pressure is 0.6 Pa, and the base layer deposition time is 30 min. Then enter the Cr coating deposition stage. The Cr coating is deposited on the sample by multi-arc ion plating technology. The selected bias is -75V, the arc target current is 100A, the coil current is 1A, the gas pressure is 2.7Pa, the zirconium alloy substrate temperature is 340℃, and the deposition time is 6h.

[0036] In some embodiments, the deflection is the downward displacement of the indenter.

[0037] In some embodiments, the test is stopped when the deflection reaches 1.7 mm.

[0038] It should be noted that the greater the first crack initiation strain of the Cr coating and the smaller the saturated crack density, the better the toughness and crack resistance of the Cr coating.

[0039] The morphology of the prepared Cr coating with a primer layer and heat treated at 700℃ is as follows: Figure 1 As shown, the prepared Cr coating is dense, with a thickness of about 13 μm, and there are no defects and microcracks inside the Cr coating and at the interface.

[0040] Figure 2 to Figure 4 The following are the crack density evolution curves, saturated crack density, first crack initiation strain and cross-sectional morphology of different Cr coating samples after three-point bending test. Sample 1 is a Cr coating sample without primer and without heat treatment, sample 2 is a Cr coating sample with primer and without heat treatment, sample 3 is a Cr coating with primer and heat treated at 650℃, sample 4 is a Cr coating with primer and heat treated at 700℃, and sample 5 is a Cr coating with primer and heat treated at 800℃.

[0041] Depend on Figure 2 and Figure 3 It can be seen that compared with the Cr coating sample without primer layer, the first crack initiation strain of the Cr coating with primer layer is increased and the saturated crack density is reduced, indicating that the crack resistance of the Cr coating with primer layer is improved. Figure 4 From sample 1 and sample 2, it can be seen that after the three-point bending test, the Cr coating sample without the primer layer showed obvious interface cracks, while the Cr coating sample with the primer layer had no interface cracks, indicating that the primer layer significantly improved the interface bonding performance of the Cr coating. In addition, compared with the Cr coating sample without heat treatment, the first crack initiation strain of the heat-treated Cr coating sample was larger and the saturated crack density was smaller, indicating that the heat treatment significantly improved the toughness and crack resistance of the Cr coating. After heat treatment at 650℃, the first crack initiation strain of the Cr coating was significantly increased from 0.45% to 4.1%, which fully met the industry requirements for the fuel cladding to resist 1% strain.

[0042] It should be noted that although higher heat treatment temperatures (such as 800°C and above) will improve the toughness and crack resistance of the Cr coating, it will also produce a brittle ZrCr2 diffusion layer at the interface between the Cr coating and the substrate. Figure 4 As shown in sample 5, under external load, cracks easily occur in the interface diffusion layer, which reduces the interface bonding performance of the Cr coating. At the same time, higher heat treatment temperatures change the microstructure and mechanical properties of the substrate, posing a threat to the comprehensive performance assessment of the cladding. Therefore, the Cr coating sample with a base layer heat treated at 650℃ to 700℃ has more excellent and balanced performance.

[0043] In summary, based on the Cr coating preparation process and heat treatment method of the present application, the anti-cracking performance and interface bonding performance of the accident-resistant Cr coating can be significantly improved while ensuring that the performance of the zirconium alloy substrate does not change significantly.

[0044] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the embodiments of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0045] The embodiments of the present application are described in detail above in conjunction with the accompanying drawings, but the present application is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in the technical field without departing from the purpose of the present application.

Claims

1. A method for improving the performance of zirconium alloy Cr coating, characterized in that: The following steps are involved: Zirconium alloy matrix pretreatment: polish the upper and lower surfaces and sides of the zirconium alloy matrix, and remove surface stains by ultrasonic cleaning; Deposition of Cr coating on zirconium alloy substrate: The zirconium alloy substrate is cleaned by high-energy ions formed by arc discharge target evaporation and ionization, and a high bias voltage and low gas pressure are used for a long time to deposit the base layer, so that the high-energy incident ions are pinned to the surface of the zirconium alloy substrate. The bias voltage of the arc discharge is -500V, the arc target current is 100A, the coil current is 1A, the gas pressure is 0.6Pa, and the base layer deposition time is 30min. Then, the Cr coating is deposited on the zirconium alloy substrate by multi-arc ion plating technology. When depositing the Cr coating, the bias voltage of the arc discharge is -75V, the arc target current is 100A, the coil current is 1A, the gas pressure is 2.7Pa, the zirconium alloy substrate temperature is 340℃, and the deposition time is 6h. Heat treatment of zirconium alloy substrate: The zirconium alloy substrate on which the Cr coating is deposited is subjected to high-temperature annealing heat treatment, wherein the heat treatment temperature is greater than the ductile-brittle transition temperature of the Cr coating and less than the recrystallization temperature of the zirconium alloy substrate.

2. The method for improving the performance of zirconium alloy Cr coating according to claim 1, characterized in that: Before the high-temperature annealing heat treatment, the zirconium alloy substrate after the Cr coating is deposited is placed in a quartz tube for vacuum packaging. After the high-temperature annealing heat treatment is completed, it is naturally cooled to room temperature in an air environment, and then the quartz tube is broken to take out the heat-treated Cr-coated zirconium alloy substrate.

3. The method for improving the performance of zirconium alloy Cr coating according to claim 2, characterized in that: The steps of placing the zirconium alloy substrate into a quartz tube for vacuum packaging are as follows: placing the zirconium alloy substrate in a quartz tube, passing argon gas into the tube for 10 minutes, and then using a vacuum pump to pump the gas in the tube into a vacuum state, and then using a tungsten wire to heat the other end of the quartz tube to a high-temperature molten state and achieve packaging to ensure that there is no oxygen in the tube.

4. The method for improving the performance of zirconium alloy Cr coating according to claim 3, characterized in that: The steps of high temperature annealing heat treatment are as follows: the muffle furnace is heated to the target temperature at a rate of 10°C / min, the target temperature is 650°C~700°C, then kept warm for 30 minutes, and then the furnace door is opened, and the packaged Cr-coated zirconium alloy substrate is quickly placed in the crucible boat in the muffle furnace for high temperature annealing heat treatment. After the temperature stabilizes to the target temperature, it is kept warm for 1 hour.

5. The method for improving the performance of zirconium alloy Cr coating according to claim 2, characterized in that: The Cr-coated zirconium alloy substrate taken out from the quartz tube after cooling after heat treatment is placed in anhydrous ethanol solution for ultrasonic cleaning.

6. A method for detecting the performance of a Cr coating, characterized in that: The following steps are involved: Prepare a zirconium alloy substrate sample containing a primer layer and a heat-treated Cr coating according to the method of claim 1; A zirconium alloy substrate sample without a primer layer and without a heat-treated Cr coating is prepared; A zirconium alloy substrate sample containing a primer layer and a Cr coating without heat treatment is prepared; The observation surfaces of the above three samples were ground and polished until the Cr coating and the substrate cross section were exposed for in-situ observation of the crack evolution information of the sample cross section. The samples were placed on the testing machine, the upper and lower pressure heads were pressed tightly, and a preload of 20N was applied to fix them. Then the three-point bending test was started. The speed of the pressure head moving downward was 0.005 mm / s. At the same time, a high-power optical microscope was used to take real-time photos of the cross-sectional morphology of the Cr coating samples to obtain the evolution data of the Cr coating crack density at different deflections. The Cr coating crack density is defined as the number of Cr coating cracks per unit area. When the deflection reaches a specific value, the test is stopped, the sample is taken out after unloading, and the test is ended. The crack density data of the sample is counted, and the toughness and crack resistance of the Cr coating are evaluated by comparing the first crack initiation strain and saturated crack density of each Cr coating sample.

7. The method for detecting the performance of Cr coating according to claim 6, characterized in that: The steps for preparing the zirconium alloy substrate sample without primer and without heat-treated Cr coating are as follows: Step 1: Cut the zirconium alloy plate into a number of three-point bending test samples, grind the upper and lower surfaces and sides of the samples with sandpaper, and then perform ultrasonic cleaning on the samples; Step 2: Place the Cr target with a purity of 99.99% in the multi-arc ion plating furnace, adjust the distance between the target and the sample to 20 cm, and perform ion cleaning on the sample surface before Cr coating. The ion cleaning is mainly divided into two steps: first, evacuate the furnace chamber to a vacuum of 1.0×10 -4 Pa, set the workpiece holder to a high bias and introduce argon gas, set a high bias of -600V to ionize the argon gas into Ar+ ions and bombard the sample surface at high speed, then turn on the arc source, and use the high-energy ions formed by the evaporation and ionization of the arc discharge target to clean the sample, then enter the Cr coating deposition stage, and deposit the Cr coating on the sample by multi-arc ion plating technology. The selected bias voltage is -75V, the arc target current is 100A, the coil current is 1A, the gas pressure is 2.7Pa, the zirconium alloy substrate temperature is 340℃, and the deposition time is 6h.

8. The method for detecting the performance of Cr coating according to claim 6, characterized in that: The steps for preparing the zirconium alloy substrate sample with the primer layer and the Cr coating without heat treatment are as follows: Step 1: Cut the zirconium alloy plate into a number of three-point bending test samples, grind the upper and lower surfaces and sides of the samples with sandpaper, and then perform ultrasonic cleaning on the samples; Step 2: Place the Cr target with a purity of 99.99% in the multi-arc ion plating furnace, adjust the distance between the target and the sample to 20 cm, and perform ion cleaning on the sample surface before Cr coating. The ion cleaning is mainly divided into two steps: first, evacuate the furnace chamber to a vacuum of 1.0×10 -4 Pa, set the workpiece support high bias and pass argon gas, set -600V high bias to ionize argon into Ar+ ions and bombard the sample surface at high speed, then turn on the arc source, use the high-energy ions formed by the evaporation and ionization of the arc discharge target to clean the sample, then enter the deposition base layer stage, use the high-energy ions formed by the evaporation and ionization of the arc discharge target to clean the zirconium alloy substrate, use high bias and low gas pressure to deposit the base layer for a long time, so that the high-energy incident ions are pinned to the surface of the zirconium alloy substrate sample, the selected bias is -500V, the arc target current is 100A, the coil current is 1A, the gas pressure is 0.6 Pa, and the base layer deposition time is 30min, then enter the Cr coating deposition stage, and deposit the Cr coating on the sample by multi-arc ion plating technology, the selected bias is -75V, the arc target current is 100A, the coil current is 1A, the gas pressure is 2.7Pa, the zirconium alloy substrate temperature is 340℃, and the deposition time is 6h.

9. The method for detecting the performance of Cr coating according to claim 6, characterized in that: The deflection is the downward displacement of the pressure head.

10. The method for detecting the performance of Cr coating according to claim 9, characterized in that: The test was stopped when the deflection reached 1.7 mm.

Citation Information

Patent Citations

  • PVD preparation technology of surface metal coating of zirconium casing for nuclear reactor

    CN108796454A

  • Preparation method of coating on zircomium alloy coverage shell

    CN109943811A

  • Method for preparing high-hardness wear-resistant composite coating on surface of zirconium alloy used in reactor

    CN110453184A

  • Preparation method of interface-integrated zirconium or zirconium alloy cladding surface functional coating

    CN111041412A

  • Method for manufacturing of Zirconium alloy cladding tubes and the Zirconium alloy cladding tubes thereby

    KR1020160005819A

Cited By

  • Annular compression detection method for zirconium alloy cladding tube

    CN121324117A